2002
DOI: 10.1210/endo.143.6.8873
|View full text |Cite
|
Sign up to set email alerts
|

ER Function in the Adult Male Rat: Short- and Long-Term Effects of the Antiestrogen ICI 182,780 on the Testis and Efferent Ductules, without Changes in Testosterone

Abstract: Male rats, 30 d old, were treated with the antiestrogen ICI 182,780 (3-150 d) to determine sequences of events leading to testicular atrophy and infertility. Plasma testosterone and LH concentrations were unchanged. ICI 182,780 induced dilation of efferent ductules as early as 3 d post treatment, and the dilation increased over time, resulting in an overall increase of 200% in tubule diameter. A gradual reduction in height of the ductule epithelium was observed; however, the microvilli height increased up to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 48 publications
8
35
0
2
Order By: Relevance
“…These testicular effects were probably a result of an accumulation of fluid following inhibition of reabsorption in the efferent ductules (Oliveira et al 2001), similar to the phenotype seen in the ER -deficient mouse (Eddy et al 1996). In a follow-up study these authors confirmed that changes in the efferent ductules preceded those in the testes indicating that the testicular effects of ICI 182780-treated rats were secondary to the epididymal effects (Oliveira et al 2002). These data confirm that the antagonist doses used in our study would be expected to substantially impair ER-mediated effects, consistent with the observation of a suppression of serum FSH in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These testicular effects were probably a result of an accumulation of fluid following inhibition of reabsorption in the efferent ductules (Oliveira et al 2001), similar to the phenotype seen in the ER -deficient mouse (Eddy et al 1996). In a follow-up study these authors confirmed that changes in the efferent ductules preceded those in the testes indicating that the testicular effects of ICI 182780-treated rats were secondary to the epididymal effects (Oliveira et al 2002). These data confirm that the antagonist doses used in our study would be expected to substantially impair ER-mediated effects, consistent with the observation of a suppression of serum FSH in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The adult ER knock-out testis is grossly dismorphic, probably due to back pressure of luminal fluids as oestrogen regulates fluid reabsorption in the head of the epididymis (Hess et al 1997). Normal rats (Oliveira et al 2001(Oliveira et al , 2002 and mice (Cho et al 2003) treated with an ER antagonist (ICI 182780) also provide compelling evidence that testicular disruption is secondary to dilation of the rete testis and efferent ductule lumens due to lack of action by an oestrogen-dependent Na + /H + exchanger necessary for fluid and electrolyte reabsorption (Zhou et al 2001). On the other hand, a lack of a direct oestrogenic effect on the seminiferous epithelium is thought to account for the phenotype seen in the ArKO mouse wherein germ cells early in spermiogenesis are the primary site of impairment with no changes being reported in spermatogonial number .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-estrogen treatment Animals were treated as previously described (Oliveira et al 2002, Yasuhara et al 2008. Rats were treated once a week for 2 months with corn oil (control group) or ICI 182,780 (10 mg/ rat, s.c., AstraZeneca), starting at an age of 30 days.…”
Section: In Vivo Treatmentsmentioning
confidence: 99%
“…Recent investigations of mice, deficient in aromatase (cyp 19 gene knockout, ArKO) (Robertson et al 1999), have provided direct evidence for a physiological role of estrogens in male reproductive organs suggesting additional direct effects of estrogens on spermatogenesis. In addition, it has been shown that anti-estrogens have detrimental effects on the morphogenesis and function of the male reproductive system (Oliveira et al 2001(Oliveira et al , 2002.…”
Section: Introductionmentioning
confidence: 99%